Is high AgNOR quantity in hepatocytes associated with increased risk of hepatocellular carcinoma in chronic liver disease?. Issue 8 (August 1993) - Derenzini, M; Trerè, D; Oliveri, F; David, E; Colombatto, P; Bonino, F; Brunetto, M R
Abstract : AIMS–To evaluate whether high numbers of silver staining nucleolar organiser regions (AgNORs) in hepatocytes are associated with increased risk of hepatocellular carcinoma in chronic liver disease. METHODS–The quantitative distribution of AgNORs was studied in the liver biopsy specimens of 33 patients with chronic liver disease, 11 of whom developed hepatocellular carcinoma. The interval between liver biopsy and diagnosis of hepatocellular carcinoma was 26 months (range one to 61 months); the mean follow up of patients without hepatocellular carcinoma was 45 months (range 24-59 months). Quantitative evaluation of AgNORs was carried out on silver stained routine sections by morphometric analysis, using a computer assisted image analysis system. RESULTS–High interphase AgNOR values (> 3 microns2) were found in hepatocytes of nine out of the 11 (82%) patients in whom neoplastic transformation occurred. Of the remaining 22 patients, only seven (31%) had AgNOR values higher than > 3 microns2 (chi 2 4.83; p = 0.036). CONCLUSIONS–These results indicate that high numbers of interphase AgNORs are associated with increased risk of hepatocellular carcinoma in patients with chronic liver disease.